Collective decision making in Tibetan macaques: how followers affect the rules and speed of group movement. (December 2018) - Rowe, Amanda K.; Li, Jin-Hua; Sun, Lixing; Sheeran, Lori K.; Wagner, R. Steven; Xia, Dong-Po; Uhey, Derek A.; Chen, Rui
Abstract : Social organisms make collective decisions during group movement, thereby remaining cohesive and providing the ecological and evolutionary benefits of sociality. The ability for groups to make successful collective decisions is dependent on relationships between leaders and followers. We investigated how consistent followers (a fan structure) facilitated successful group movement in a group of Tibetan macaques, Macaca thibetana, at Mt. Huangshan in Anhui, China. We used structural equation modelling to determine the relative influences of sex, age, number of maternal familial connections within the group, dominance and social network centrality on the number of fans that an individual had and the number of other group members that an individual was a fan of (fandom). Our structural equation modelling revealed that dominant females had more fans, while younger, dominant individuals with more familial connections were fans of more individuals. Fans and fandom were most strongly influenced by dominance, displaying a strong network of females occupying top positions in the dominance hierarchy who consistently followed each other. In addition, we examined the relationship between fan structure and movement speed and success. Using regression, we found a positive relationship between fans and speed and a negative correlation between fans and number of unsuccessful movements, suggesting a link between the social connections maintained in a movement and the speed of the movement. Dominant females with more fans initiated slower movements, perhaps because the complex fan structure slowed the joining process. However, individuals with more fans led fewer unsuccessful movements, suggesting a relationship between fans and initiation success. Our findings show a network of social relationships within Tibetan macaque groups that are used during movement organization to maintain cohesion and mediate the benefits of sociality. Highlights: We studied Tibetan macaque decision making during collective movement. Dominant females had the most consistent followers during movement. Dominant, younger individuals with more kin consistently followed more individuals. Individuals with more consistent followers led slower movements. Individuals with more consistent followers had fewer unsuccessful movement initiations.